Effect of a concomitant elemental diet with maintenance anti‐tumor necrosis factor‐α antibody therapy in patients with Crohn's disease: A multicenter, prospective cohort study. Issue 1 (16th July 2018) - Hirai, Fumihito; Ishida, Tetsuya; Takeshima, Fuminao; Yamamoto, Shojiro; Yoshikawa, Ichiro; Ashizuka, Shinya; Inatsu, Haruhiko; Mitsuyama, Keiichi; Sou, Suketo; Iwakiri, Ryuichi; Nozaki, Ryoichi; Ohi, Hidehisa; et al.
Abstract: Background and Aim: The aim of this study was to clarify the additional effect of a concomitant elemental diet (ED) for patients with Crohn's disease on maintenance anti‐tumor necrosis factor‐α antibody (anti‐TNF). Methods: Crohn's disease patients who received anti‐TNF induction therapy were enrolled. Patients who achieved clinical response (defined as delta Crohn's disease activity index [CDAI] > 70 and CDAI < 200) at 10–14 weeks after the start of infliximab or adalimumab were included. Eligible patients took a tolerability test of ED (900 kcal/day) for 3 days. Then, patients who preferred concomitant ED and whose ED tolerance was confirmed were allocated to the ED group and given Elental 900 kcal/day or more. Other patients were allocated to the non‐ED group. The primary endpoint was the cumulative remission rate at 2 years after baseline. Clinical relapse was defined as CDAI > 200 and/or need for additional treatment. Adherence to the ED was confirmed at each visit. Results: Seventy‐two patients were included. Thirty‐seven were allocated to the ED group, and 35 were allocated to the non‐ED group. The cumulative remission rate at 2 years was not significantly different between the two groups (60.9% vs 56.7%, P = 0.98). Adherence to the ED in the ED group was relatively low, and only 11 patients were maintained on an ED of 900 kcal/day. Conclusions: The addition of ED for Crohn's disease patients who responded to initial anti‐TNF induction therapy was not found to improve outcomes. The efficacy of concomitant ED in other clinical settings, such as loss of response, needs to be clarified in the future (UMIN000009789).